INFLUENCE OF COMPANY IMAGE, CUSTOMER EXPERIENCE ON SATISFACTION AND ITS IMPACT ON REPURCHASE INTENTION - Khoirur Roziqin; Endang Tjahjaningsih (Jurnal Ekonomi, 2023)
More and more coffee shops are opening in Indonesia, especially in Semarang. To obtain satisfaction and the likelihood of repurchasing intents from the diverse customer perspectives about how the company's reputation and their own shopping experience pan out. This study examines how company image and customer experience affect consumer satisfaction and repurchase intentions. Purposive sampling was used as the method for gathering samples for this investigation. By handing out questionnaires that are scored on a Likert scale, a selection of 100 responders is obtained. Multiple linear regression analysis will be used to examine the data that has been collected. According to the study, corporate image and customer experience variables positively and significantly influenced contentment, whereas the satisfaction variable positively and significantly influenced repurchase intention.